The commons in an age of uncertainty: a review essay - Duchrow, Ulrich (The American journal of economics and sociology, 2021)
Franklin Obeng-Odoom's recent work offers an alternative to both conventional economics and to what he calls the 'Western left consensus.' Obeng-Odoom's option involves placing justice at the center of policy regarding commons, not as a side note. Justice requires a focus on the land issue. This much is true, but Obeng-Odoom ignores the plurality of views that are critical of the dominant political economy. A successful transition to a sustainable future will make use of many cultural and religious traditions working together.